LITERASI MEDIA SOSIAL DALAM PENDIDIKAN NON FORMAL - Isro'i, Nurul Faqih (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2018)
This paper provides an overview of social media literacy education in non-formal education. Social media literacy is needed so that the use of social media will be much healthier with positive content and can bring benefits for yourself, community, nation and country. Media literacy is a media literacy movement designed to enhance individual control over the media used to send and receive messages. Media literacy can be viewed as a skill that can be developed. Opportunities to develop media literacy movements, especially social media are very large in the portion of non-formal education. Training in non-governmental organizations, discussions, seminars, can be done maximally within the scope of non-formal education. Finally, it is hoped that with literate on social media, people become smart in utilizing the media in everyday life.